2020
DOI: 10.7181/acfs.2019.00612
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between fresh and cryopreserved fat injections in facial lipofilling

Abstract: Background: Autologous fat is considered an ideal filler material, and the use of cryopreserved fat grafts is promising in terms of flexibility and efficiency. Therefore, cryopreserved fat grafts have become more common in recent years; however, their complications require further consideration. Methods: We evaluated 53 patients who underwent facial lipofilling at our institution to confirm the clinical usefulness and safety of cryopreserved fat. Fresh fat injections with or without cryopreserved fat were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Studies both in vitro and in vivo were conducted to assess whether the cold was toxic to the adipocytes and whether cell survival was affected by decreasing the storage temperature from 4°C to −80°C, but yet to provide a uniform conclusion. [10][11][12][13][14] Some studies indicate that there were no significant differences between the fresh and cryopreserved fat injections. 14,15 While in other studies, the results are different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies both in vitro and in vivo were conducted to assess whether the cold was toxic to the adipocytes and whether cell survival was affected by decreasing the storage temperature from 4°C to −80°C, but yet to provide a uniform conclusion. [10][11][12][13][14] Some studies indicate that there were no significant differences between the fresh and cryopreserved fat injections. 14,15 While in other studies, the results are different.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Some studies indicate that there were no significant differences between the fresh and cryopreserved fat injections. 14,15 While in other studies, the results are different. Melike et al 10 have demonstrated that the viability of fat grafts stored at 4°C provides the highest number of viable adipocytes compared with dry, frozen samples (−20°C and −80°C) for at least 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AFI’s main obstacle in augmentation is an unpredictable outcome from a high absorption rate and necrosis at the grafted site [ 14 ]. For acute inflammation after fat grafting, good results can be obtained by re-transplanting fat after treatment for inflammation [ 15 ]. However, in this case of patients who visited the hospital due to persistent chronic inflammation, it was judged that the possibility of recurrence would be high if the fat was re-transplanted.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, no study has reported the effect of frozen fat grafters on the rate of volume retention during longer follow-up periods [ 8 , 9 ]. Moreover, frozen fat face injection has been found to have a similar clinical effect to fresh facial fat injection [ 10 ]. Cryopreservation of adipose tissue is accompanied by various problems, key among them cooling and thawing temperatures, as well as the use of cryopreservation agents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%